Blended Learning and Student Outcomes: A Qualitative Study of Teachers’ Lived Experiences - Sadoughi, Mitra; Esmaeilpour, Maghsoud (Assessment and Practice in Educational Sciences, 2026)
This qualitative study aimed to explore and analyze the lived experiences of teachers implementing blended learning (combining in-person and virtual modalities) to enhance student engagement and academic achievement. Adopting an exploratory design and employing thematic analysis, the study involved female elementary school teachers in Mazandaran Province, Iran. Participants were purposefully selected through snowball sampling. Data were collected via semi-structured interviews with 15 teachers conducted in school settings, continuing until theoretical saturation was reached. To ensure the trustworthiness of the findings, both participant validation and expert review were employed. Data analysis yielded six major themes contributing to improved student engagement and academic outcomes: (1) quality of in-person and virtual teaching, (2) promotion of deep learning, (3) effective instructional strategies, (4) influence of the learning environment, (5) professional development and teacher training, and (6) cultural and social factors. Furthermore, 17 sub-themes were identified, including the use of blended learning tools, technology interaction, diverse learning resources, active teaching methods, learning environment design, and adaptation to students’ individual characteristics.